DIMENSI PENDIDIKAN SHALAT BAGI MANUSIA (Kajian Kritis terhadap Tasyri’ Shalat) - Said, Ali (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This article intends to examine the educational dimensionof shalat for humans. Through the concept offered by law, prayer isnot only a means of ritual expression of a servant to worship God,let alone just a religious duty that must be met by all adherentswithout understanding the function and mission execution of suchobligations. Shalat is the lessons learned from the discipline of thetime, speech, movement, concentration, and packed full compliancein the theme of prayer which include; cognitive, affective andpsychomotor. Therefore to understand prayer as a whole, then theprayer is, and must also be understood for whom prescribedprayers, which in turn indicates that the recipes offered throughprayer will be able to understand and be understood, thisunderstanding will realize the importance of prayer actors for him,and in the end the prayer performed with high awareness, withoutcompulsion. If everything was done voluntarily and happily, thencomfort will arise, naturally, instinctively, people who feelcomfortable life then certainly it would be a good person, a goodperson will always do things that are good also. Changed and thesechanges are an indication of the success of obliged praying forhumans. Humans who received correctly and continuously everyday five times a person will definitely be righteous, namely, ashshaalihiinthat according to Quran is a group of people who aredevoted to God and who joined the group of prophets, people whoalways true, and the martyrs.Keywords: Education prayer, shalat